1993
DOI: 10.1182/blood.v82.7.2010.2010
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of response to recombinant human erythropoietin in patients with the anemia of renal failure by serum transferrin receptor and fibrinogen

Abstract: Recombinant human erythropoietin (rHuEpo) has been shown to be effective in correcting the anemia of chronic renal failure, but the dose needed may be variable. The reason for this variation is not known, but several factors could be involved, such as iron deficiency, inflammation, aluminum intoxication, hyperparathyroidism, blood losses, or marrow dysfunction. Treatment with rHuEpo was given intravenously thrice weekly after hemodialysis to 64 consecutive unselected patients with the anemia of chronic renal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The semilogarithmic relationship between the serum Epo and the blood haemoglobin concentration in leishmaniasis patients was compared to the one in a reference group of persons not suffering from inflammation, as described recently ( El Hassan et al , 1997 ). The observed/predicted (O/P) ratio of log [Epo] was calculated for each serum sample according to Beguin et al (1993 ).…”
Section: Methodsmentioning
confidence: 99%
“…The semilogarithmic relationship between the serum Epo and the blood haemoglobin concentration in leishmaniasis patients was compared to the one in a reference group of persons not suffering from inflammation, as described recently ( El Hassan et al , 1997 ). The observed/predicted (O/P) ratio of log [Epo] was calculated for each serum sample according to Beguin et al (1993 ).…”
Section: Methodsmentioning
confidence: 99%
“…Resistance to Epo in inflammation and infection is mainly caused by the action of IFN‐ γ and TNF‐ α (314). Measurements of C‐reactive protein and baseline fibrinogen concentrations in serum may enable early recognition of the probability of response to Epo (315).…”
Section: Anaemia Of Renal Failurementioning
confidence: 99%
“…However, haemoglobin should be monthly checked in patients with erythropoiesis stimulating agent initiation for dose adjustments to assess its response [15]. Beguin et al [30] reported 2 groups of responder to rHuEpo treatment; respond within 3 months after baseline examination (early responders) and respond 3-6 months after baseline examination (late responders). In clinical practice, it is proposed that at least 1-2 months is needed to observe a signi cant response to rHuEpo by monitoring the erythrocyte indices; haemoglobin or haematocrit [15,16].…”
Section: Discussionmentioning
confidence: 99%